'Giving Voice to Values': enhancing students' capacity to cope with ethical challenges in legal practice. (3rd July 2015) - Holmes, Vivien
ABSTRACT: Legal ethics pedagogy does not often attend to the gap between principles and effective action. A pedagogy that does attend to this gap is 'Giving Voice to Values' (GVV). Developed by a US business academic, Mary Gentile, GVV focuses not on the normative questions of 'what is the right thing to do?' but on the behavioural question 'how do we get the right thing done?' GVV has much to offer efforts to foster ethical behaviour in lawyers. In this article, I situate GVV within the behavioural ethics literature, which examines how and why people make the decisions they do in the ethical realm. I then turn to a discussion of the GVV curriculum and a case study of its application in legal education. I report preliminary results from research into the effectiveness of the GVV approach in postgraduate practical legal training. Finally, I encourage legal ethics teachers to experiment with GVV as a way of helping students develop skills for dealing constructively with ethical challenges in legal practice.